A Survey of Backfilling Algorithms in Cloud Resource Allocation - Nisha, V; Vimala, S (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing is an information technology (IT) paradigm that enables ubiquitous access to shared pools of configurable system resources and higher-level services that has provisioned with minimal management effort over the Internet. The main enabling technology for cloud computing is Virtualization, which is essentially creating scalable system of multiple independent computing devices. With virtualization, idle computing resources have allocated to user more effectively. Allocation of idle computing resource is one of the major problem faced today in cloud computing. Adopting to right resource allocation algorithms can resolve the problem of resource allocation. Backfilling algorithms are better than the existing First Come First Serve algorithms (FCFS) used for resource allocation. In this paper, various `Backfilling` algorithms are surveyed. Further analysis on the performance of each algorithm in terms of response time, throughput, waiting time, turn-around time, job migration between queues are measured.